Penerapan Teknologi Reproduksi untuk Mempertahankan Ketersediaan Ayam Upakara di Bali - Suartha, I N.; Bebas, I W; Mahardika, I. G.N.K. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi, 2016)
Chicken is important part in Balinese Hindu ceremony. Chicken were used as ceremony are chicken with black feather (siap selem), red feather (siap biing), white feather (siap putih) that a white feather chicken with white colour feet, yellow feather (siap putih siungan), that a white feather chicken with yellow colour feet, and chicken with mixed colour of those four colour (siap brumbun). Limitations of technology owned by community makes the chicken’s breeding doesn’t provide economic added value. The purpose of this service is to provide innovation of artificial insemination technology of chicken production for ceremony. The Innovation is given through counseling and workshops . The results showed that people knowledge about disease and breeding management was increased. The farmer have been able to do artificial insemination and vaccination in chicken. The participant were very enthusiastic in following the activities and understand the disease and how to prevent diseases in chickens. These skills are need to trained constantly to find the comfortable thechnique. The conclusions is farmers have been able to perform artificial insemination in chicken.
Keywords: Reproductive technology, Artificial Insemination, Ceremony, Chicken, Bali